A novel ternary memory property achieved through rational introduction of end-capping naphthalimide acceptors. Issue 31 (27th July 2017) - Zhang, Qijian; He, Jinghui; Li, Hua; Li, Najun; Xu, Qingfeng; Chen, Dongyun; Lu, Jianmei
Abstract : Small molecule-based multilevel rewritable memory devices have gained attention because they possess super-high storage density, can sustain the stored data without power supply and erase/rewrite electrically; however, formation of these memory devices is extremely hard to achieve. Abstract : Small molecule-based multilevel rewritable memory devices have recently gained extensive attention because they possess super-high storage density and can sustain the stored data without power supply and erase and rewrite electrically; however, small molecule-based multilevel flash-type memory device is extremely challenging to achieve. Herein, we designed a symmetric molecule with end-capping naphthalimide acceptors through rational tuning. This molecule showed an improved crystal size and uniform crystal orientation in the film state. The sandwich-structured device exhibited the typical WORM (write-once–read-many times) memory property from OFF to ON1 transition and encouraging flash memory behavior for the ON1/ON2 transition. This is the first report on small molecule-based ternary memory devices with rewritable memory behavior, and this study will inspire the exploration of multilevel data-storage devices with fully rewritable properties in the subsequent researches.